Using molecular phylogenetics and species distribution modeling to test the role of orogeny and paleoclimate change in driving allopatry in a frog of the northern Colombian Andes (2017)
"We evaluate the role of the Northern Andes high peaks and the Magdalena Valley, creating barriers to dispersal and promoting vicariance among mid-elevation populations of Rheobates palmatus (Aromobatidae). Frog populations are limited to the eastern and western flanks of the Eastern Cordillera and the eastern flank of the Central Cordillera. We analyze mitochondrial and nuclear DNA sequences from 41 individuals inferring the divergence times and vicariance scenarios and species distribution models to analyze the role of climatic variables in determining the presence geographic boundaries of the species. The phylogeny of Rheobates is largely predicted by geography, but we detected paraphyletic lineages on the eastern side of the Eastern Cordillera and we detected unanticipated latitudinal phylogeographic structure within the western flank of the Eastern Cordillera." -- Tomado del Formato de Documento de Grado.